Efeito da linhagem, densidade de criação e sistemas de produção de frangos de corte sobre as condenações por abscessos e dermatoses - Torezan, Guilherme Baú (2019)
The consumption of chicken meat has been increasing every year, besides the greater demand from international markets, there is a constant increase in consumption by Brazilians. In this context, Paraná is the Brazilian state that produces and exports the most chicken in the country. The increase in production and demand for this protein raises the concern of industries regarding quality and yield, as there is a need to get larger and heavier chickens in less time. This rapid development of birds increases the incidence of diseases, especially skin lesions such as abscess and dermatosis, which generates losses because of convictions. In this sense, the present work aims to evaluate incidences of convictions for abscesses and dermatosis in broilers, in the period of 2016 and 2018, of a slaughterhouse in the north of Paraná considering the shed (automated, semi-automated and non-automated); densities and lines of broiler chicken (Cobb®, Ross®, Hubbard®) used and correlating the variables. Thus, based on the findings of the company and the Federal Inspection Service - SIF and using the stepwise method for the selection of variables, a negative binomial regression model was determined to assess the incidence of abscesses and dermatosis for three consecutive years. We observed an increase in the number of abscesses between the years 2016 and 2018, it relates these values to the increased use of the Ross® strain. Using the non-automatic chicken rearing system reduced the occurrence of abscesses, whereas the other sheds and density did not have a significant effect on the occurrence of abscesses. The density and the automatic system had a significant influence in the reduction of dermatosis. The Ross® strain is the one that most influenced the increase in the number of birds with dermatosis while Hubbard® showed a tendency to decrease. Dermatosis and abscess corresponded to the first and third place among the causes of the counties and were responsible for an average annual loss of R$ 485.845,00, besides partial convictions that were not included in this calculation. The present study, therefore, pointed out the paths to be followed to reduce these conditions based on management, use of commercial types and facilities.